Cascade double isocyanide insertion and C–N coupling of 2-iodo-2′-isocyano-1, 1′-biphenyls. Issue 21 (16th May 2018) - Sun, Hongwei; Tang, Shi; Li, Dengke; Zhou, Yali; Huang, Jinbo; Zhu, Qiang
Abstract : This reaction provides the first example of using a functionalized isocyanide in double insertion to construct nitrogen-containing heterocyclic systems. Abstract : A palladium-catalyzed double isocyanide insertion using 2-iodo-2′-isocyano-1, 1′-biphenyls followed by copper-catalyzed intramolecular C–N coupling, delivering a unique heterocyclic structure containing both phenanthridine and carbazole scaffolds, has been developed. In this cascade process, four chemical bonds, including two C–C, one C–O, and one C–N bonds are formed consecutively without isolating an intermediate. The strategy of using a functionalized isocyanide in double insertion provides a quick approach for constructing heterocyclic systems with high bond-forming efficiency.